Method for regulating biomass-based hard carbon microstructure by vapor deposition, biomass-based hard carbon negative electrode materials and applications

Through vapor deposition, the method of regulating the biomass-based hard carbon microstructure is solved, and the problem of low efficiency of the first circle of the biomass-based hard carbon negative electrode material is achieved, achieving higher battery cycle stability and capacity.

CN119284882BActive Publication Date: 2025-03-04SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411806565.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing biomass-based hard carbon anode material has low efficiency in the first circle of the sodium ion battery, resulting in unstable battery performance.

Method used

The method of regulating the biomass-based hard carbon microstructure through vapor deposition includes pre-oxidation treatment of the biomass-based nut shell, heat treatment under an inert atmosphere containing organic molecules, and finally carbonization treatment to modify the surface defects of the hard carbon and form an orderly surface structure.

Benefits of technology

The first-circle Coulomb efficiency of the biomass-based hard carbon anode material during the charging and discharging process is improved, the cycle stability of the battery is enhanced, and the high capacity characteristics are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284882B_ABST
    Figure CN119284882B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery material technology, and in particular to a method for regulating biomass-based hard carbon microstructure by vapor deposition, biomass-based hard carbon negative electrode material and application, the method comprising the steps of: pre-oxidizing the biomass-based fruit shell, heat-treating the pre-oxidized fruit shell under an inert atmosphere containing organic molecules to obtain a hard carbon material precursor; and finally carbonizing the hard carbon material precursor. By using an inert gas as a carrier gas to mix gaseous organic molecules, the atmosphere of high-temperature sintering hard carbon is changed, and the organic molecules are deposited on the surface of the hard carbon precursor, so that the lignin-rich fruit shell biomass base can controllably form a relatively ordered surface structure during the carbonization process, and the surface defects of the hard carbon are modified to obtain a biomass-based hard carbon negative electrode active material, so that the solid electrolyte interface generated by contact with the electrolyte during the charge and discharge process is thinner and chemically stable, and the first-cycle coulomb efficiency is improved while maintaining high capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a method for regulating a biomass-based hard carbon microstructure by vapor deposition, a biomass-based hard carbon negative electrode material and its application. Background Art

[0002] Biomass hard carbon-based negative electrode materials for sodium-ion batteries are considered to be the most promising negative electrode materials for sodium-ion batteries due to their wide sources, low prices, and environmental friendliness. The biomass precursor has a rich pore structure, and the hard carbon material formed by pyrolysis continues this structural feature. Although these rich pores and defects can provide considerable sodium storage capacity, they will produce adverse side reactions when in contact with the electrolyte, resulting in excessive sodium ions being irreversibly embedded in the hard carbon material, which in turn causes the problem of low first-cycle coulombic efficiency (ICE).

[0003] Many research works have focused on adjusting the pores of the material to avoid side reactions by reducing pores and defects. However, such methods inevitably lose the inherent high caloric value of biomass-based hard carbon.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method for regulating the microstructure of biomass-based hard carbon by vapor deposition, a biomass-based hard carbon negative electrode material and its application, aiming to solve the problem of low first-cycle coulombic efficiency that is common in biomass-based hard carbon negative electrode materials prepared by existing methods.

[0006] The technical solution of the present invention is as follows:

[0007] A method for regulating biomass-based hard carbon microstructure by vapor deposition, comprising the steps of:

[0008] Pre-oxidizing the biomass-based fruit shell to obtain pre-oxidized fruit shell;

[0009] The pre-oxidized fruit shell is heat-treated in an inert atmosphere containing organic molecules to obtain a hard carbon material precursor;

[0010] The hard carbon material precursor is carbonized to complete vapor deposition and regulation of biomass-based hard carbon microstructure.

[0011] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the mass content of lignin in the biomass-based fruit shell is between 30% and 75%.

[0012] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the biomass-based fruit shells include one or more of peanut shells, pine nut shells, hazelnut shells, almond shells, and walnut shells.

[0013] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the pre-oxidation treatment is carried out in an air atmosphere; the temperature of the pre-oxidation treatment is 250°C-350°C, the time of the pre-oxidation treatment is 3h-5h, and the heating rate of the pre-oxidation treatment is 3°C / min-5°C / min.

[0014] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the organic molecules include one or more of ethyl acetate, ethanol, ethyl ether, acetone, isoamyl acetate, and n-hexane.

[0015] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the temperature of the heat treatment is 900°C-1000°C, the time of the heat treatment is 2h-3h, and the heating rate of the heat treatment is 3°C / min-5°C / min.

[0016] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the gas flow rate of the inert atmosphere containing organic molecules is 25sccm-30sccm.

[0017] The method for regulating biomass-based hard carbon microstructure by vapor deposition, wherein the temperature of the carbonization treatment is 1300°C-1500°C, the time of the carbonization treatment is 2h-3h, and the heating rate of the carbonization treatment is 3°C / min-5°C / min.

[0018] A biomass-based hard carbon negative electrode material is obtained by utilizing a method for regulating the biomass-based hard carbon microstructure by vapor deposition.

[0019] Application of a biomass-based hard carbon negative electrode material in sodium ion batteries.

[0020] Beneficial effects: The present invention provides a method for regulating biomass-based hard carbon microstructure by vapor deposition, a biomass-based hard carbon negative electrode material and application. The method for regulating biomass-based hard carbon microstructure by vapor deposition comprises the following steps: pre-oxidizing biomass-based fruit shells to obtain pre-oxidized fruit shells; heat-treating the pre-oxidized fruit shells in an inert atmosphere containing organic molecules to obtain a hard carbon material precursor; carbonizing the hard carbon material precursor to complete vapor deposition to regulate the biomass-based hard carbon microstructure. The present invention uses an inert gas as a carrier gas to mix gaseous organic molecules to change the atmosphere of high-temperature sintering of hard carbon. The organic molecules are deposited on the surface of the hard carbon precursor, so that the lignin-rich biomass-based fruit shell can controllably form a relatively ordered surface structure during the carbonization process, and the surface defects of the hard carbon are modified to complete the regulation of the biomass-based hard carbon microstructure, thereby obtaining a biomass-based hard carbon negative electrode active material, so that the solid electrolyte interface generated by the contact with the electrolyte during the charge and discharge process is thinner and the chemical properties are stable, while maintaining a high capacity. The first-cycle coulomb efficiency is improved, and the effect of high cycle stability is also achieved; the method is simple and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of a process flow of a method for regulating biomass-based hard carbon microstructure by vapor deposition;

[0022] Figure 2 This is a SEM image of the biomass-based hard carbon negative electrode material prepared in Example 1;

[0023] Figure 3 TEM image of the biomass-based hard carbon negative electrode material prepared in Example 1;

[0024] Figure 4 This is a SEM image of the biomass-based hard carbon negative electrode material prepared in Comparative Example 1;

[0025] Figure 5 TEM image of the biomass-based hard carbon negative electrode material prepared in Comparative Example 1;

[0026] Figure 6 This is a data graph showing the BET specific surface area test results of the biomass-based hard carbon negative electrode materials prepared in Example 1 and Comparative Example 1;

[0027] Figure 7 The first cycle charge and discharge curves of the biomass-based hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 as the negative electrode of a sodium ion battery;

[0028] Figure 8 This is a comparison chart of the rate performance of the biomass-based hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 as the negative electrode of a sodium ion battery;

[0029] Fig. 9A comparison chart of the cycle performance of the biomass-based hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 as the negative electrode of a sodium ion battery;

[0030] Fig.10 This is a charge and discharge curve of the first cycle of the biomass-based hard carbon negative electrode material prepared in Example 2 as the negative electrode of a sodium ion battery;

[0031] Fig.11 This is a charge and discharge curve of the first cycle of the biomass-based hard carbon negative electrode material prepared in Example 3 as the negative electrode of a sodium ion battery;

[0032] Fig.12 This is the first cycle charge and discharge curve of the biomass-based hard carbon negative electrode material prepared in Comparative Example 2 as the negative electrode of a sodium ion battery. DETAILED DESCRIPTION

[0033] The present invention provides a method for vapor deposition to regulate biomass-based hard carbon microstructure, biomass-based hard carbon negative electrode material and application. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0034] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0035] like Figure 1 As shown, the present invention provides a method for regulating biomass-based hard carbon microstructure by vapor deposition, comprising the steps of:

[0036] Step S10: pre-oxidizing the biomass-based fruit shell to obtain pre-oxidized fruit shell;

[0037] Step S20: heat-treating the pre-oxidized fruit shell in an inert atmosphere containing organic molecules to obtain a hard carbon material precursor;

[0038] Step S30: performing carbonization treatment on the hard carbon material precursor to complete vapor deposition and control of biomass-based hard carbon microstructure.

[0039] In this embodiment, an inert gas is used as a carrier gas to mix gaseous organic molecules to change the atmosphere of high-temperature sintering of hard carbon. Organic molecules are deposited on the surface of the hard carbon precursor, so that the lignin-rich fruit shell biomass base can controllably form a relatively ordered surface structure during the carbonization process. The surface defects of the hard carbon are modified to complete the regulation of the biomass-based hard carbon microstructure, and a biomass-based hard carbon negative active material is obtained. The solid electrolyte interface produced by contact with the electrolyte during the charge and discharge process is thinner and chemically stable, thereby improving the first-cycle coulomb efficiency while maintaining high capacity and having the effect of high cycle stability. This method is simple and easy to mass produce.

[0040] Specifically, the present invention can quickly achieve the regulation of the surface defect structure of biomass-based hard carbon by changing the inert atmosphere without modifying the equipment on the basis of the existing technical path, and realize the controllable growth of graphite-like domains, thereby providing a high first-cycle coulomb efficiency for sodium-ion batteries without losing reversible capacity, and improving the cycle stability of the battery. The first-cycle coulomb efficiency of the biomass-based hard carbon negative electrode material as the negative electrode of the sodium-ion battery is increased from 73-75% to about 90%, and the reversible capacity reaches more than 343.32mAh / g.

[0041] In some embodiments, the lignin mass content of the biomass-based fruit shell is between 30% and 75%. The biomass-based fruit shell with a high lignin mass content is used as a raw material for preparing hard carbon negative electrode materials. It has a wide source and low cost. After the above-mentioned preparation process, a biomass-based hard carbon negative electrode material with high first-cycle coulombic efficiency can be obtained.

[0042] In a preferred embodiment, the lignin mass content of the biomass-based fruit shell is 40%-60%. The biomass-based fruit shell with a lignin mass content within the above range is easy to obtain and provides abundant and adjustable carbon flakes for the material carbonization process.

[0043] In some embodiments, the biomass-based fruit shells include but are not limited to one or more of peanut shells, pine nut shells, hazelnut shells, almond shells, and walnut shells. The above-mentioned biomass-based fruit shells have a higher lignin mass content. After the above-mentioned preparation process, a biomass-based hard carbon negative electrode material with high first-cycle coulomb efficiency can be obtained.

[0044] In a preferred embodiment, the biomass-based fruit shells include one or more of pine nut shells, almond shells, and walnut shells.

[0045] In some embodiments, the pre-oxidation treatment is performed in an air atmosphere; the temperature of the pre-oxidation treatment is 250°C-350°C, the time of the pre-oxidation treatment is 3h-5h, and the heating rate of the pre-oxidation treatment is 3°C / min-5°C / min.

[0046] Specifically, the pre-oxidation treatment can avoid the rapid release of a large amount of volatile substances during the high-temperature carbonization process, which leads to structural collapse and the formation of undesirable voids; in addition, the oxygen-rich active centers formed during the pre-oxidation process will promote the formation of cross-links and hinder the growth of graphite-like structures during the subsequent carbonization process. This long-range ordered structure of graphitization is not conducive to the deintercalation of sodium ions during the charge and discharge process.

[0047] In a preferred embodiment, the temperature of the pre-oxidation treatment is 300° C., the time of the pre-oxidation treatment is 4 hours, and the heating rate of the pre-oxidation treatment is 4° C. / min; preliminary coking of the biomass-based product is achieved.

[0048] In some embodiments, the organic molecules include but are not limited to one or more of ethyl acetate, ethanol, ether, acetone, isoamyl acetate, and n-hexane. The above organic molecules adhere to the surface of the carbon material at low temperatures, and the alkyl small molecules produced at high temperatures preferentially interact with the defective positions on the pre-oxidized fruit shell, so that the edges of the originally short-range ordered carbon layers are linked to each other to form a medium-range ordered structure, which can avoid the deposition of metallic sodium clusters, thereby avoiding the continuous irreversible decomposition of the electrolyte.

[0049] In some embodiments, in step S20, the method of heat treating the pre-oxidized fruit shell in an inert atmosphere containing organic molecules includes the steps of: washing the inert gas through the organic molecule solution at a gas flow rate of 30mL / min-50mL / min; allowing the inert gas to carry the organic molecules to form an organic molecule carrier gas environment.

[0050] In some embodiments, the heat treatment temperature is 900°C-1000°C, the heat treatment time is 2h-3h, and the heating rate of the heat treatment is 3°C / min-5°C / min. Heat treatment within this parameter range can remove tar and preliminarily form a hard carbon framework structure; at the same time, the alkyl small molecules produced by organic molecules in the high temperature range will preferentially interact with the defective positions on the pre-oxidized fruit shell, so that the edges of the originally short-range ordered carbon layers are linked to each other to form a medium-range ordered structure. This structure can avoid the deposition of metallic sodium clusters, thereby avoiding the continuous irreversible decomposition of the electrolyte.

[0051] In a preferred embodiment, the temperature of the heat treatment is 950° C., the time of the heat treatment is 2 h, and the heating rate of the heat treatment is 4° C. / min.

[0052] In some embodiments, the gas flow rate of the inert atmosphere containing organic molecules is 25sccm-30sccm; sufficient organic molecules can be provided for the pre-oxidized fruit shells, so that the alkyl small molecules produced by the organic molecules under the high temperature range will preferentially interact with the defect positions on the pre-oxidized fruit shells, so that the edges of the originally short-range ordered carbon layers are linked to each other to form a medium-range ordered structure.

[0053] In some embodiments, the temperature of the carbonization treatment is 1300°C-1500°C, the time of the carbonization treatment is 2h-3h, and the heating rate of the carbonization treatment is 3°C / min-5°C / min. Under this condition, the hard carbon material precursor is carbonized to decompose the cellulose, hemicellulose and lignin contained in the biomass base, and the functional groups such as hydroxyl and carboxyl groups are dehydrated, decarboxylated, dehydrogenated, etc., and the carbon chains and carbon atoms are rearranged to form a disordered structure.

[0054] Specifically, after the hard carbon material precursor obtained by heat treatment in an inert atmosphere containing organic molecules is naturally cooled and annealed, it is directly carbonized at a carbonization temperature of 1400°C, a carbonization time of 2h, and a carbonization heating rate of 4°C / min.

[0055] In some embodiments, the carbonization process is directly performed under an inert atmosphere to provide an air-isolating effect.

[0056] In some embodiments, the inert gas includes but is not limited to one or more of argon, nitrogen, and helium, which can be used to isolate the heat treatment and carbonization from air and prevent the carbon material and oxygen from being lost in the form of carbon dioxide at high temperatures.

[0057] In addition, the present invention also provides a biomass-based hard carbon negative electrode material, which is obtained by a method of regulating the biomass-based hard carbon microstructure by vapor deposition.

[0058] In this embodiment, the biomass-based hard carbon negative electrode active material obtained by modifying the surface defects of hard carbon using the preparation method can produce a thinner solid electrolyte interface with stable chemical properties when in contact with the electrolyte during the charge and discharge process, thereby improving the first-cycle coulombic efficiency while maintaining high capacity and having the effect of high cycle stability. The method is simple and easy to mass produce.

[0059] In addition, the present invention also provides an application of a biomass-based hard carbon negative electrode material in a sodium ion battery.

[0060] In this embodiment, the present invention obtains a biomass-based hard carbon negative electrode material by changing the inert atmosphere to quickly achieve the regulation of the surface defect structure of the biomass-based hard carbon, realize the controllable growth of graphite-like domains, and then provide a high first-cycle coulomb efficiency for the sodium ion battery without losing the reversible capacity, thereby improving the cycle stability of the battery. When the biomass-based hard carbon negative electrode material is applied to a sodium ion battery, the assembled half-cell exhibits a first-cycle coulomb efficiency of up to 90% at a current density of 50 mAh / g, which is significantly improved compared to the original biomass-based hard carbon sintered without loading organic molecules.

[0061] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0062] Example 1

[0063] This embodiment provides a biomass-based hard carbon negative electrode material, and the preparation steps are as follows:

[0064] Step 1: Crush the walnut shells, weigh about 200 g of sample, place it in a muffle furnace in an air atmosphere at 300 ° C for pre-oxidation, keep it warm for 3 hours, and cool it to room temperature.

[0065] Step 2: Use a graphite crucible to transfer the sample to a tubular furnace with a special inert atmosphere. The argon gas introduced into the tubular furnace has passed through a gas washing bottle containing ethyl acetate in advance. In the atmosphere of the organic solvent carrier gas, the temperature is increased to 1000°C at a rate of 5°C / min and kept at this temperature for 2 hours. The gas flow rate is 25sccm.

[0066] Step 3: After cooling to room temperature, remove the washing bottle to ensure that the sample does not come into contact with air, heat it to 1400°C at a heating rate of 5°C / min under normal argon atmosphere, keep it warm for 2 hours, and cool it to room temperature to obtain the optimized lignin-rich biomass-based hard carbon negative electrode material.

[0067] The biomass-based hard carbon negative electrode material obtained in this example was characterized, and its microscopic morphology (SEM) is as follows: Figure 2 The carbon layer arrangement obtained by transmission electron microscopy (TEM) is shown in Figure 3 As shown, it can be observed that the material has a relatively regular medium-range ordered arrangement structure.

[0068] Comparative Example 1

[0069] Step 1: Crush the walnut shells, weigh about 200 g of sample, place it in a muffle furnace in an air atmosphere at 200 ° C for pre-oxidation, keep it warm for 3 hours, and cool it to room temperature.

[0070] Step 2: Use a graphite crucible to transfer the sample to a conventional inert atmosphere tube furnace, heat it to 1000°C at a heating rate of 5°C / min, and keep it at this temperature for 2h with a gas flow rate of 25sccm.

[0071] Step 3: After cooling to room temperature, remove the gas washing bottle to ensure that the sample does not come into contact with air, heat it to 1400°C at a heating rate of 5°C / min in a normal argon atmosphere, keep it warm for 2 hours, and cool it to room temperature. Obtain a comparative unoptimized lignin-rich biomass-based hard carbon negative electrode material.

[0072] The biomass-based hard carbon negative electrode material obtained in this comparative example was characterized, and its microscopic morphology is as follows Figure 4 The carbon layer arrangement obtained by transmission electron microscopy (TEM) is shown in Figure 5 shown.

[0073] The BET specific surface area test results of the biomass-based hard carbon negative electrode materials prepared in Example 1 and Comparative Example 1 are as follows: Figure 6 As shown, the porosity increased compared to the untreated comparative example 1.

[0074] The biomass-based hard carbon negative electrode material prepared in Comparative Example 1 was used as the active material to assemble a sodium ion battery button half-cell, using a commercial electrolyte of 1.0 M NaPF6 / DEGDME and metal Na as the counter electrode. The electrochemical performance test was carried out at a current density of 50 mAh / g. The first cycle charge and discharge curve is shown in Figure 7 As shown in the figure, the first cycle coulombic efficiency is only 72.4% and the reversible capacity is 259.81 mAh / g. The comparison sample is a conventional method for processing biomass hard carbon, and the pretreatment and heat treatment processes are not optimized.

[0075] The biomass-based hard carbon negative electrode material prepared in Example 1 was used as the active material to assemble a sodium ion battery button half-cell, using a commercial electrolyte of 1.0 M NaPF6 / DEGDME and metal Na as the counter electrode. The electrochemical performance test was carried out at a current density of 50 mAh / g. The first cycle charge and discharge curve is shown in Figure 7 As shown, compared with the comparative example 1 without special carrier gas treatment, the first cycle coulomb efficiency of Example 1 was as high as 90%, and the reversible capacity reached 343.32 mAh / g; the rate performance of the biomass-based hard carbon negative electrode material prepared in Example 1 and the comparative example 1 as the negative electrode of the sodium ion battery is as shown in Figure 8 As shown, compared with the comparative example 1 without special carrier gas treatment, the cycle performance of the biomass-based hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 as the negative electrode of the sodium ion battery is shown in Fig. 9 As shown, the stability of the material during the charge and discharge cycle is improved.

[0076] Example 2

[0077] This embodiment provides a biomass-based hard carbon negative electrode material, and the preparation steps are as follows:

[0078] Step 1: Crush the walnut shells, weigh about 200 g of sample, place it in a muffle furnace in an air atmosphere at 300 ° C for pre-oxidation, keep it warm for 3 hours, and cool it to room temperature.

[0079] Step 2: Use a graphite crucible to transfer the sample to a tubular furnace with a special inert atmosphere. The argon gas introduced into the tubular furnace passes through a wash bottle containing ethyl acetate in advance. In the atmosphere of the organic solvent carrier gas, the temperature is increased to 900°C at a rate of 5°C / min and kept at this temperature for 2 hours. The gas flow rate is 25sccm.

[0080] Step 3: After cooling to room temperature, remove the washing bottle to ensure that the sample does not come into contact with air, heat it to 1400°C at a heating rate of 5°C / min in a normal argon atmosphere, keep it warm for 2 hours, and cool it to room temperature. The optimized lignin-rich biomass-based hard carbon anode material is obtained.

[0081] The above biomass-based hard carbon negative electrode material was used as the active material to assemble a sodium ion battery button half-cell, using commercial electrolyte 1.0 M NaPF6 / DEGDME and metal Na as the counter electrode. The electrochemical performance test was carried out at a current density of 20 mAh / g. The first cycle charge and discharge curve is shown in Fig.10 As shown, the first-cycle coulombic efficiency was 83% and the reversible capacity reached 319.81 mAh / g.

[0082] Example 3

[0083] This embodiment provides a biomass-based hard carbon negative electrode material, and the preparation steps are as follows:

[0084] Step 1: Crush the walnut shells, weigh about 200 g of sample, place it in a muffle furnace in an air atmosphere at 200 ° C for pre-oxidation, keep it warm for 3 hours, and cool it to room temperature.

[0085] Step 2: Use a graphite crucible to transfer the sample to a tubular furnace with a special inert atmosphere. The argon gas introduced into the tubular furnace has passed through a gas washing bottle containing ethanol in advance. In the atmosphere of the organic solvent carrier gas, the temperature is increased to 1000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours. The gas flow rate is 25sccm.

[0086] Step 3: After cooling to room temperature, remove the washing bottle to ensure that the sample does not come into contact with air, heat it to 1400°C at a heating rate of 5°C / min in a normal argon atmosphere, keep it warm for 2 hours, and cool it to room temperature. The optimized lignin-rich biomass-based hard carbon anode material is obtained.

[0087] The above biomass-based hard carbon negative electrode material was used as the active material to assemble a sodium ion battery button half-cell, using commercial electrolyte 1.0 M NaPF6 / DEGDME and metal Na as the counter electrode. The electrochemical performance test was carried out at a current density of 20 mAh / g. The first cycle charge and discharge curve is shown in Fig.11 As shown, the first-cycle coulombic efficiency was 85% and the reversible capacity reached 329.53 mAh / g.

[0088] Comparative Example 2

[0089] This embodiment provides a biomass-based hard carbon negative electrode material, and the preparation steps are as follows:

[0090] Step 1: Crush the walnut shells, weigh about 200 g of sample, place it in a muffle furnace in an air atmosphere at 200 ° C for pre-oxidation, keep it warm for 3 hours, and cool it to room temperature.

[0091] Step 2: Use a graphite crucible to transfer the sample to a conventional inert atmosphere tube furnace, heat it to 1000°C at a heating rate of 5°C / min, and keep it at this temperature for 2h with a gas flow rate of 25sccm.

[0092] Step 3: After cooling to room temperature, remove the gas washing bottle to ensure that the sample does not come into contact with air, and heat to 1400°C at a heating rate of 5°C / min in a normal argon atmosphere, keep warm for 2 hours, and cool to room temperature.

[0093] Step 4: Use a graphite crucible to transfer the sample to a tubular furnace with a special inert atmosphere. The argon gas introduced into the tubular furnace has passed through a gas washing bottle containing ethyl acetate in advance. In the atmosphere of the organic solvent carrier gas, the temperature is increased to 1000°C at a heating rate of 5°C / min and kept at this temperature for 2 hours. The gas flow rate is 25sccm.

[0094] Step 5: After cooling to room temperature, remove the gas washing bottle to ensure that the sample does not come into contact with air, and heat to 1400°C at a heating rate of 5°C / min in a normal argon atmosphere, keep warm for 2 hours, and cool to room temperature. Comparative sample 2 is obtained.

[0095] The above biomass-based hard carbon material was used as the active material to assemble a sodium ion battery button half-cell, using a commercial electrolyte of 1.0 M NaPF6 / DEGDME and metal Na as the counter electrode. The electrochemical performance test was carried out at a current density of 20 mAh / g. The first cycle charge and discharge curve is shown in Fig.12 As shown, the first cycle coulombic efficiency is 86% and the reversible capacity is 279.14 mAh / g. This ratio sample can judge that the organic small molecules play a role in regulating the arrangement of hard carbon during the 1000°C heat treatment, rather than the traditional coating effect. If the 1400°C carbonization treatment is performed first and then the organic small molecule carrier gas heat treatment is performed, the effect is similar to the coating treatment, and the electrochemical performance cannot achieve the ideal effect in the embodiment.

[0096] In summary, the present invention provides a method for vapor deposition regulation of biomass-based hard carbon microstructure, a biomass-based hard carbon negative electrode material and application. The method for vapor deposition regulation of biomass-based hard carbon microstructure includes the steps of: pre-oxidizing biomass-based fruit shells to obtain pre-oxidized fruit shells; heat-treating the pre-oxidized fruit shells in an inert atmosphere containing organic molecules to obtain a hard carbon material precursor; carbonizing the hard carbon material precursor to complete vapor deposition regulation of the biomass-based hard carbon microstructure. The present invention uses an inert gas as a carrier gas to mix gaseous organic molecules to change the atmosphere of high-temperature sintering of hard carbon. The organic molecules are deposited on the surface of the hard carbon precursor, so that the lignin-rich fruit shell biomass base can controllably form a relatively ordered surface structure during the carbonization process, and the surface defects of the hard carbon are modified to complete the regulation of the biomass-based hard carbon microstructure, thereby obtaining a biomass-based hard carbon negative electrode active material, so that the solid electrolyte interface generated by contact with the electrolyte during the charge and discharge process is thinner and the chemical properties are stable, while maintaining a high capacity. The first-cycle coulomb efficiency is improved, and the effect of high cycle stability is also achieved; the method is simple and easy to mass produce.

[0097] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for regulating biomass-based hard carbon microstructure by vapor deposition, characterized in that: Includes steps: Pre-oxidizing the biomass-based fruit shell to obtain pre-oxidized fruit shell; The pre-oxidized fruit shell is heat-treated in an inert atmosphere containing organic molecules to obtain a hard carbon material precursor; Carbonizing the hard carbon material precursor to complete vapor deposition and regulate the biomass-based hard carbon microstructure; The lignin mass content of the biomass-based fruit shell is between 40% and 60%; The pre-oxidation treatment is carried out in an air atmosphere; the temperature of the pre-oxidation treatment is 250°C-350°C, the time of the pre-oxidation treatment is 3h-5h, and the heating rate of the pre-oxidation treatment is 3°C / min-5°C / min; The organic molecules include one or more of ethyl acetate, ethanol, ether, acetone, isoamyl acetate, and n-hexane; the inert atmosphere includes one or more of argon, nitrogen, and helium; The temperature of the heat treatment is 900°C-1000°C, the time of the heat treatment is 2h-3h, and the heating rate of the heat treatment is 3°C / min-5°C / min; the temperature of the carbonization treatment is 1300°C-1500°C, the time of the carbonization treatment is 2h-3h, and the heating rate of the carbonization treatment is 3°C / min-5°C / min.

2. The method for regulating biomass-based hard carbon microstructure by vapor deposition according to claim 1, characterized in that: The biomass-based nut shells include one or more of peanut shells, pine nut shells, hazelnut shells, almond shells, and walnut shells.

3. The method for regulating biomass-based hard carbon microstructure by vapor deposition according to claim 1, characterized in that: The gas flow rate of the inert atmosphere containing organic molecules is 25 sccm-30 sccm.

4. A biomass-based hard carbon negative electrode material, characterized in that: The biomass-based hard carbon microstructure is obtained by using the method for regulating the biomass-based hard carbon microstructure by vapor deposition as described in any one of claims 1 to 3.

5. An application of the biomass-based hard carbon negative electrode material as claimed in claim 4 in a sodium ion battery.

Citation Information

Patent Citations

  • Biomass hard carbon negative electrode material of sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material

    CN116621153A

Cited By

  • Asphalt-based hard carbon / graphite composite material with nano closed pores and preparation method of asphalt-based hard carbon / graphite composite material

    CN120246984A

  • Sodium-ion battery hard carbon negative electrode material based on step-by-step cooperative regulation and preparation method

    CN122254472A